2006
DOI: 10.1086/510067
|View full text |Cite
|
Sign up to set email alerts
|

A Thermal Wind Model for the X-Ray Outflow in GRO J1655-40

Abstract: Recent Chandra observations of an outflowing gas in GRO J1655-40 resulted in a suggestion by Miller et al. (2006) that the wind in this system must be powered by a magnetic process that can also drive accretion through the disk around the black hole. The alternative explanations, of radiation pressure or thermally driven flows, were considered unsatisfactory because of the highly ionized level of the gas and because of the derived small distance from the black hole, well inside the minimum distance required fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 12 publications
2
66
0
Order By: Relevance
“…code ION (Netzer 2006) with an H-atom containing 40 levels, solar abundances, hydrogen density of 10 10 cm −3 , column density of 10 23 cm −2 and ionization parameter of 10 −1.5 . The exact shape is insensitive to the exact value of these parameters and the normalization is done by direct fits to the observations.…”
Section: Thin Disk Continuum Approachmentioning
confidence: 99%
“…code ION (Netzer 2006) with an H-atom containing 40 levels, solar abundances, hydrogen density of 10 10 cm −3 , column density of 10 23 cm −2 and ionization parameter of 10 −1.5 . The exact shape is insensitive to the exact value of these parameters and the normalization is done by direct fits to the observations.…”
Section: Thin Disk Continuum Approachmentioning
confidence: 99%
“…From a detailed analysis of the absorption line profile, they detected multiple components in the wind, where a more ionized part was located at a smaller radius. After Miller et al (2006) first reported the Chandra/HETG result, the unusual wind in GRO J1655−40 has been revisited many times from both observational and theoretical points of view (Netzer 2006;Miller et al 2008;Kallman et al 2009;Luketic et al 2010;Neilsen & Homan 2012;Higginbottom & Proga 2015). Many previous studies were based on the assumption that the wind was optically thin and launched at a few percent of the Eddington luminosity, in constructing photoionized plasma models and performing hydrodynamic simulations.…”
Section: Where Is the Hidden Compton-thick Wind Located?mentioning
confidence: 99%
“…In 2005, a remarkable wind from GRO J1655−40 was detected with the Chandra High Energy Transmission Grating (HETG) (Miller et al 2006(Miller et al , 2008Netzer 2006). The observed spectrum exhibited a rich forest of blueshifted ionized absorption lines.…”
Section: Introductionmentioning
confidence: 99%
“…Most follow up studies have supported the magnetic origin of the wind (Neilsen & Homan 2012, and references therein). However, thermally-driven winds remain a possibility (Netzer 2006). …”
Section: Introductionmentioning
confidence: 99%